Utilization of Banana Pseudostem Biomass Waste and Coconut Pulp as Briquettes for Alternative Energy Sources: Utilization of Banana Pseudostem Biomass Waste and Coconut Pulp as Briquettes for Alternative Energy Sources - Mellyta Uliyandari; Asep Supriatna; Eka Cahaya Prima (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
This study aims to utilize banana pseudostem and coconut pulp waste as raw materials for biomass briquettes, evaluate their physical and thermal characteristics, and assess their potential as alternative fuel sources. The research methods included drying, grinding, mixing, molding, and briquette testing. Characterization was conducted through hardness testing using a digital sclerometer, morphological and particle size analysis using a digital microscope, calorific value measurement using a bomb calorimeter, and thermal degradation analysis using Thermogravimetric Analysis (TGA). The hardness test showed that pure banana pseudostem briquettes had the highest compressive strength according to the P3HH standard, while the addition of coconut pulp tended to reduce it. Increasing the proportion of coconut pulp produced larger average particle sizes, affecting briquette porosity. The highest calorific value, 16,829.73 J/g, was obtained from a 50:50 composition, indicating that the oil and lignin content in coconut pulp contributes to combustion energy. TGA analysis revealed that briquettes with higher banana pseudostem content exhibited greater heat resistance, while those with more coconut pulp ignited faster and left less residue. In conclusion, briquettes made from banana pseudostem and coconut pulp can be used as an alternative solid fuel, with compositions adjustable according to the desired energy output and combustion characteristics.